Quality and Shelf Life of Dried Sharks Produced in India - Mathen, Cyriac (Fishery Technology, 1970)
The landings of elasmobranch fishes in India during the past nine years averaged 35,227 metric tons of which major contributions were from Madras, Kerala, Andhra, Gujarat, Maharashtra and Mysore in descending order of quantity. Major portion of the catch is converted to cured products and either exported to Ceylon and other far eastern countries or consumed internally. Though compulsory pre-shipmnent inspection was introduced recently, not much is known about the quality of the commercial products. This note deals with the quality and shelf life of dried sharks produced in India. Salting shark flesh in 1:3 ratio and allowing to cure in self brine for more than 12 hours followed by drying give the product with a satisfactory shelf life.